PEMETAAN STRUKTUR PASAR DAN POLA DISTRIBUSI TELUR AYAM RAS PENYUMBANG INFLASI DAERAH SERTA IMPLIKASINYA TERHADAP KEBIJAKAN PENGENDALIAN HARGA - Bramantika Oktavianti (Faculty of Economics and Business Mulawarman University, 2013)
General purpose of this study is to identify the market structure, distribution patterns and behavior of commodity producers eggs regional contributor to inflation. So it is known for certain commodities which contributed to inflation in Samarinda. Based on the above description and analysis of several important points can be drawn as follows: Market structure is formed in each level and the majority are perfectly competitive oligopoly market due to the nature and characteristics of a homogeneous commodity and a mass commodity. The majority of respondents at the level of retailers stated that the supply is not interrupted if the respondent did not commit distribution of commodities, is inversely proportional to the respondents on the label distributors and manufacturers.Keywords: Market Structure, distribution patterns, the behavior of producers and local inflation.